1991
DOI: 10.1073/pnas.88.9.3715
|View full text |Cite
|
Sign up to set email alerts
|

c-rel activates but v-rel suppresses transcription from kappa B sites.

Abstract: We show that the product of the protooncogene c-rel is a constituent of an NF-#cB-like complex that binds to the id site originally identified in the enhancer of immunoglobulin K light chain gene. c-rel protein synthesized in bacteria binds to the ic site in a sequence-specific manner. The rel-,cB complex can be disrupted by incubation with anti-rel antibodies. The rel protein can form oligomers. The c-rel protein can activate transcription from promoters containing icB sites; v-rel, on the other hand, suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
116
1
2

Year Published

1991
1991
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 44 publications
4
116
1
2
Order By: Relevance
“…When this sequence was disrupted by certain mutations, the transforming and transcriptional repressing abilities of v-Rel were impaired and c-Rel showed reduced cytoplasmic retention in CEF. suggested that the oncogenicity of v-Rel is based on its ability to repress promoters containing NF-KB binding sites, either through DNA binding or protein-protein interactions (3,14,15,22,33 Our results suggest that the phosphorylation of Ser-275 could have an inhibitory effect on transformation by v-Rel. Consistent with this suggestion, Ser-275 does not appear to be a major phosphorylation site in vivo in v-Rel in transformed spleen cells, even in the presence of okadaic acid (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…When this sequence was disrupted by certain mutations, the transforming and transcriptional repressing abilities of v-Rel were impaired and c-Rel showed reduced cytoplasmic retention in CEF. suggested that the oncogenicity of v-Rel is based on its ability to repress promoters containing NF-KB binding sites, either through DNA binding or protein-protein interactions (3,14,15,22,33 Our results suggest that the phosphorylation of Ser-275 could have an inhibitory effect on transformation by v-Rel. Consistent with this suggestion, Ser-275 does not appear to be a major phosphorylation site in vivo in v-Rel in transformed spleen cells, even in the presence of okadaic acid (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Similar transfection studies with p50 have failed to demonstrate transcriptional activation functions (7,57,60,64). Other studies have demonstrated that both c-rel and dorsal have activation domains within the C-terminal region (12,20,26,29,30,57). In contrast, by using an in vitro transcription assay, it has been shown that the rel homology domain of p50 is capable of transcriptional activation (19,39).…”
mentioning
confidence: 88%
“…For example, because v-Rel is a relatively weak activator of transcription, high-level expression of v-Rel reduces transcription from kB site-containing promoters in cells that have constitutively nuclear kB-site activating complexes (Inoue et al, 1991;Ishikawa et al, 1993;McDonnell et al, 1992;Richardson and Gilmore, 1991;Walker et al, 1992). That is, v-Rel homodimers displace more strongly activating complexes, such as ones containing RelA or c-Rel, and reduce the level of transcription.…”
Section: Dna Binding By V-relmentioning
confidence: 99%
“…Moreover, because v-Rel can form heterodimers with endogenous Rel proteins and transcriptionally activate their genes, the analysis of e ects of v-Rel on kB site-containing promoters can become somewhat muddled in vertebrate cells. Therefore, many experiments that have investigated transcriptional activation of kB site promoters by v-Rel have been performed in cell types that lack endogenous Rel proteins, such as in yeast, Drosophila cells, mouse F9 teratocarcinoma cells or human Tera-2 embryonal carcinoma cells, all of which lack endogenous kB sitebinding activity Inoue et al, 1991;Ishikawa et al, 1993;Kamens and Brent, 1991;Mosialos and Gilmore, 1993;Sachdev et al, 1997).…”
Section: Dna Binding By V-relmentioning
confidence: 99%